The Influence Of Brand Awareness, Brand Image, And Brand Trust On The Decision To Purchase Fried Chicken At Albaik Kampung Bali Branch In Bengkulu City - Aisyah Putri Utami; Ida Anggriani; Abdul Rahman (Penerbit Jurnal Indonesia, 2024)
In today's companies, they are required to compete competitively (competition rivalry) which creates and maintains loyal consumers (more specifically called customers), and one of them is through “war between brands”. In the era of globalization, producers are faced with competition to achieve brand dominance. This research aims to determine the influence of Brand Awareness, Brand Image and Brand Trust on the decision to purchase Fried Chicken at Albaik Branch, Kampung Bali, Bengkulu City. The sample in this study was 52 customers who had purchased fried chicken at Albaik Branch, Kampung Bali, Bengkulu City. Data collection techniques by questionnaires. The analytical method used is Multiple Regression analysis, t hypothesis test and f hypothesis test. The regression results show that there is a positive influence between Brand Awareness, Brand Image and Brand Trust on purchasing decisions at Albaik Branch, Kampung Bali, Bengkulu City because the direction of the regression has a positive direction, namely Y = 7,300 + 0.240X1 + 0.401X2 + 0.157X3. Brand Awareness has an influence but is not significant on purchasing decisions at Albaik Branch, Kampung Bali, Bengkulu City, because the significant value of 0.89 is greater than 0.05. This means that as attention to Brand Awareness decreases, purchasing decisions will decrease. The image brand has a significant influence on the decision to purchase fried chicken at Albaik Branch in Kampung Bali, Bengkulu City because the significant value of 0.005 is smaller than 0.05. This illustrates that as the Brand Image increases, purchasing decisions increase. Brand Trust has an influence but is not significant on the decision to purchase fried chicken Albaik Branch, Kampung Bali, Bengkulu City, because the significant value of 0.77 is greater than 0.05. This means that decreasing attention to Brand Trust will reduce the decision to purchase fried chicken at Albaik Branch, Kampung Bali, Bengkulu City. Brand Awareness, Brand Image, and Brand Trust have a significant influence together on the decision to purchase fried chicken at Albaik Branch, Kampung Bali, Bengkulu City, thus the initial hypothesis proposed is proven (Ha is accepted), namely there is a significant influence between Brand Awareness, Brand Image and Brand Trust on purchasing decisions together. The coefficient of determination of R square is 0.543. This means that Brand Awareness, Brand Image and Brand Trust influence purchasing decisions by 54.3% while the remainder (100-54.3%=45.7%) is influenced by other factors not examined in this research.